Influence of preheating on performance of circular carbide inserts in end milling of carbon steel - A.K.M., Nurul Amin; Abraham, Irwan; Nor, Khairusshima; Ahmed, Mirghani Ishak (Elsevier, 2007)
Circular inserts have much higher tool life as compared to conventional rectangular inserts because of their capability to be indexed through small angles for repeated use. Their only limitation is high chattering tendencies due to high contact length in conjunction with small uncut chip thickness. Experimental investigations were conducted to investigate the influence of preheating on performance of circular cemented carbides inserts in end milling operation of mild steel performed on vertical machining center (VMC) with rigid structure. Three TiN-coated circular cemented carbide inserts fitted on a 32 mm diameter tool were used in the experiments. Variable cutting parameters were cutting speed and feed. Depth of cut was kept constant at 1 mm. Performance of the inserts under room temperature and preheated machining was compared in terms of vibration stability, surface roughness, tool life and chip integrity. Vibration signals were recorded using an accelerometer type transducer and a Dual Channel Portable Signal Analyzer. The recorded signals were analyzed using the PULSE Labshop software. Surface roughness values were measured using a surface roughness measuring instrument-Mitutoyo Surfacetest model SJ-400. Worn tools and pitches of serrated chip teeth were studied under a scanning electron microscope (SEM). It was observed that during machining with and without preheating the main chatter frequencies remained practically constant and close to the natural frequencies of the system components while the amplitudes varied with cutting conditions. The amplitudes of chatter during preheating were found to be much lower than those during room temperature machining, as a result of which the surface roughness and tool wear were found to be much lower during preheated machining. The effect of chatter was also reflected on chip serration and segmentation. It was also observed that feed rate and cutting speed have considerable effect on surface roughness and tool wear in the cases of both hot and room temperature machining.